Legal Analysis Of Victims Of Defamation Through Social Media Reviewed From Ite Law No. 19 of 2016 - M Qiefajri Adzantha; Lidya Rahmadhani Hasibuan; Muhammad Arif Sahlep (CV. AFDIFAL MAJU BERKAH, 2024)
This study is a legal analysis of victims of defamation crimes through social media, viewed from the perspective of ITE Law No 19 of 2016. In Decision Number 108/Pid.B/2023/PN Mdl, the victim experienced defamation through social media platforms.This case illustrates how the perpetrator used social media to spread information that damaged the victim's reputation. However, this study highlights that the decision did not fully consider the rights of the victim in accordance with the provisions of ITE Law No 19 of 2016, which regulates the protection of defamation victims in the digital era.This research is conducted with a descriptive approach using qualitative methods with normative juridical research types based on secondary data sources taken from court decision case studies and laws with analysis using relevant legal materials. The results of this study show that the final court decision did not fully comply with the prevailing laws in Indonesia in upholding the rights of defamation victims through social media. Judges should further consider the psychological and social impacts experienced by the victims, as well as provide more just and adequate compensation in accordance with ITE Law No 19 of 2016. Therefore, this study suggests that future legal decisions should be more favorable to victims and comprehensively consider the impacts of defamation crimes through social media.